2020
DOI: 10.1039/d0en01001d
|View full text |Cite
|
Sign up to set email alerts
|

The role of metal oxide nanoparticles,Escherichia coli, andLactobacillus rhamnosuson small intestinal enzyme activity

Abstract: To understand the effects of engineered nanomaterials added intentionally and unintentionally to food, we improved a gastrointestinal in vitro model using in vitro digested nanoparticles, Caco-2/HT29-MTX cells and gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 117 publications
1
13
0
Order By: Relevance
“…The relative abundance of Lactobacillus was significantly higher in the co-exposure group compared to in the BPA-only group, with significant differences being observed between the BPA5 and corresponding BPA5Ti100 groups ( p < 0.05). An in vitro study showed that the coexistence of Lactobacillus with nanoparticles weakened the nano-effects by controlling enzyme production [ 45 ]. Additionally, Lactobacillus_gasseri has been discovered to be a cause of Fournier’s gangrene and can produce ROS such as H 2 O 2 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Lactobacillus was significantly higher in the co-exposure group compared to in the BPA-only group, with significant differences being observed between the BPA5 and corresponding BPA5Ti100 groups ( p < 0.05). An in vitro study showed that the coexistence of Lactobacillus with nanoparticles weakened the nano-effects by controlling enzyme production [ 45 ]. Additionally, Lactobacillus_gasseri has been discovered to be a cause of Fournier’s gangrene and can produce ROS such as H 2 O 2 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This tendency is commonly seen when sonicating metal oxide suspensions as their surface atoms get excited and react with neighboring NPs forming ionic bonds. 36 Nevertheless, the ICP-MS results showed that MgO partially dissociated into ionic Mg 2+ when immersed in water, bacterial medium (completed BHI + 0.01% agar), and when partially (stomach) or fully (intestine) in vitro digested (Fig. 2G).…”
Section: Discussionmentioning
confidence: 94%
“…47 However, our previous study revealed that simulated human digestion has a strong impact on metal oxide NPs' size and reactivity. 36 Therefore, to realistically understand the impact of food additive MgO on commensal bacteria, we performed in vitro digestion of MgO and thereafter assessed its structural changes. Primary particles of the food additive MgO presented the conventional cubic structure with a mean size of approximately 65 nm, although MgO aggregated forming 200 nm particles when suspended in sterile MΩ water (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies identified negative biological consequences, for example an increased intestinal inflammation, decreased cell viability and depolarization of mitochondrial membranes, induced by the ZnO NP treatment [ 11 , 12 ]. Others showed rather inconclusive results that could not demonstrate ZnO NP toxicity in some assays, for instance an unmodified monolayer permeability but a disrupted brush border membrane [ 13 17 ], or concluded the innocuousness of a ZnO NP exposure [ 18 23 ]. The toxicity seems to depend on the used cell model, among other factors [ 24 ].…”
Section: Introductionmentioning
confidence: 99%